Farm-level adaptation to climate change: The case of the Loam region in Belgium. (September 2018) - de Frutos Cachorro, Julia; Gobin, Anne; Buysse, Jeroen
Abstract: Few studies have addressed the topic of farmers' adaptation to climate change from a multidisciplinary perspective, because of the difficulty in assessing their impacts. In view of the growing concern in the agricultural sector on this issue, we analyzed farm-level adaptation through arable land-use changes in the specific case of the Loam region in Belgium. With this aim, we used an agro-economic model which considered 20-year series of current and projected simulated yields with and without considering additional farming practices to reduce crop stress, such as irrigation and soil and water conservation techniques. Agronomic results show that climate change will negatively affect summer crop yields, particularly sugar beet and potatoes. However, we also show that adaptation to climate change through land-use changes can compensate for crop yield losses and lead to utility gains. These are obtained by reducing the share of land allocated to summer crops and barley and by increasing the surface allocated to less vulnerable crops such as winter wheat. Finally, irrigation practices would not be justified in the Loam region under climate change, since their use would incur important financial costs for farmers. Highlights: An agro-economic model for land-use adaptation to climate change is proposed. Climate change negatively affects summer root crops. Land-use adaptation would economically compensate for crop yield losses. Gains from adaptation can reach 14% in the Loam region in Belgium.